Keawetan dan Stabilitas Dimensi Papan Partikel Hibrida Bambu-Kayu dengan Perlakuan Steam dan Perendaman Panas (Durability and Dimensional Stability of Hybrid Particleboard of Bamboo-Wood with Steam and Hot Water Immersion Treatment) - Wahyu Hidayat; Intan F Suri; Rahmat Safe’i; Christine Wulandari; Wisnu Satyajaya; Indra G Febryano; Fauzi Febrianto (Masyarakat Peneliti Kayu Indonesia, 2019)
Development of bamboo as an alternative material for particleboard production has been increasing due to its fast growth, high productivity, high strength property, and light weight. The aims of this study were to determine the effects of particle pre-treatment on the durability and dimensional stability of particleboard. Particles were made from betung (Dendrocalamus asper)/B, jabon (Anthocepallus cadamba)/J, and sengon (Falcataria moluccana)/S pretreated by steam and hot water immersion. Five combinations of particleboard consisted of three homogenous boards (B-B-B, J-J-J, S-S-S) and two hybrid-particleboards (J-B-J, S-B-S) were manufactured using urea formaldehyde of 10% resin level and target density of 0.6 g cm-3. Durability of particleboards was evaluated by grave-yard test and the dimensional stability of particeboards was determined by measuring thickness swelling during a wet-dry cyclic test. The results showed that pre-treatment on particles significantly improved the durability and dimensional stability of the boards, showing lower weight loss and thickness swelling than control boards. Homogenous wood particleboards (J-J-J and S-S-S boards) showed higher weight loss and thickness swelling than bamboo particleboard (B-B-B), combining wood and bamboo particles into hybrid-particleboards (J-B-J and S-B-S boards) has improved the durability and dimensional stability of the boards.